2020
DOI: 10.3390/md18050265
|View full text |Cite
|
Sign up to set email alerts
|

Fish-Based Bioactives as Potent Nutraceuticals: Exploring the Therapeutic Perspective of Sustainable Food from the Sea

Abstract: Recent developments in nutraceuticals and functional foods have confirmed that bioactive components present in our diet play a major therapeutic role against human diseases. Moreover, there is a huge emphasis on food scientists for identifying and producing foods with better bioactive activity, which can ultimately provide wellness and well-being to human health. Among the several well-known foods with bioactive constituents, fish has always been considered important, due to its rich nutritional values and by-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 103 publications
0
63
0
1
Order By: Relevance
“…Around two-thirds of the world population (7.8 billion) is dependent on plant-based materials for their medicinal and healing properties, mainly because of their easy availability, accessibility, affordability, and safety, as well as the traditional beliefs of the consumers [ 104 ]. A very old quote by Hippocrates stated, “Let food be thy medicine and medicine be thy food”, which described the significance of food and its nutritional, as well as therapeutic, values for the prevention, treatment, and management of diseases [ 105 ]. Thereafter, DeFelice coined the term nutraceutical by merging “nutrition” and “pharmaceutical” and defined it as food or part of a food that not only imparts health benefits but, also, contributes to the prevention or treatment of various diseases [ 106 ].…”
Section: Therapeutic Prospects Of Okra As Dietary Medicine/nutracementioning
confidence: 99%
“…Around two-thirds of the world population (7.8 billion) is dependent on plant-based materials for their medicinal and healing properties, mainly because of their easy availability, accessibility, affordability, and safety, as well as the traditional beliefs of the consumers [ 104 ]. A very old quote by Hippocrates stated, “Let food be thy medicine and medicine be thy food”, which described the significance of food and its nutritional, as well as therapeutic, values for the prevention, treatment, and management of diseases [ 105 ]. Thereafter, DeFelice coined the term nutraceutical by merging “nutrition” and “pharmaceutical” and defined it as food or part of a food that not only imparts health benefits but, also, contributes to the prevention or treatment of various diseases [ 106 ].…”
Section: Therapeutic Prospects Of Okra As Dietary Medicine/nutracementioning
confidence: 99%
“…DeFelice was the first to introduce the word "nutraceutical" by coalescing the two words "nutrition" and "pharmaceutical" and define it as "food or a part of food which not only impart health benefits but also contributes in preventing or treating various diseases". Moreover, in broad terms nutraceuticals can be summarized as bioactive components which play a vital role in human beings by maintaining their normal physiological functions and well-being [10,54]. Notably, nutraceuticals have been designed in such a way, that it could be useful for the betterment and maintenance of human health without causing any harm due to their natural occurrence [55,56].…”
Section: Cordycepin As a Nutraceutical And Its Role In Human Healthmentioning
confidence: 99%
“…Currently, it has been observed that a majority of the population from developed as well as developing countries are suffering from chronic diseases, and the underlying causes are believed to be rapid urbanization and changes in eating and lifestyle behavior. Among the various underline causes, eating habits are considered one of the major risk factors for chronic diseases, such as obesity, diabetes, hypertension, hyperlipidemia and many more affecting both wellness and the wellbeing of mankind [9,10]. Therefore, the scientific community is working relentlessly to develop naturally occurring or naturally derived product, such as nutraceuticals, which could help in improving the human health status while not possessing harmful effects.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction and utilization of protein hydrolysates and peptides from fish by-products have shown numerous health-promoting properties (Syed et al, 2020). In particular, compound peptides extracted from by-products of sharks, including Prionace glauca (Rodriguez-Diaz et al, 2011), Carcharhinus limbatus (Kittiphattanabawon et al, 2012), and Mustelus mustelus (Sayari et al, 2015) have antioxidant activities and angiotensin-converting enzyme inhibitor (ACE-I) activities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, modulation of immune function through fish protein hydrolysates and peptides has also been reported to be an effective and efficient strategy in dietary treatment (Chalamaiah et al, 2018). A number of studies have reported the use of fish protein hydrolysates and peptides against acute inflammatory reactions, with the effects mostly occurring at the posttranscriptional stage, similar to the properties of anti-inflammatory drugs (Chalamaiah et al, 2018;Syed et al, 2020).…”
Section: Introductionmentioning
confidence: 99%